U-Pb LA-ICPMS dating using accessory mineral standards with variable common Pb - Kamber, Balz; Chew, David (My University, 2014)
Precise and accurate U?Pb LA-ICPMS dating of many U-bearing accessory minerals (e.g. apatite, allanite, titanite and rutile) is often compromised by common Pb. LA-ICPMS dating of these U-bearing accessory phases typically requires a matrix-matched standard, and data reduction is often complicated by variable incorporation of common Pb not only into the unknowns but particularly into the reference material. We present here a general approach to common Pb correction in U?Pb LA-ICP-MS dating using a modified version of the VizualAge U-Pb data reduction package for Iolite (VizualAge_UcomPbine). The key feature of the method is that it can correct for variable amounts of common Pb in any U-Pb accessory mineral standard as long as the standard is concordant in the U/Pb (and Th/Pb) systems following common Pb correction. Common Pb correction of the age standard can be undertaken using either the 204Pb, 207Pb or 208Pb(no Th) methods, and the approach can be applied to raw data files from all widely used modern multi-collector and single-collector ICPMS instruments. VizualAge_UcomPbine first applies a common Pb correction to the user-selected age standard integrations and then fits session-wide ?model? U-Pb fractionation curves to the time-resolved U-Pb standard data. This downhole fractionation model is applied to the unknowns and sample-standard bracketing (using a user-specified interpolation method) is used to calculate final isotopic ratios and ages. 204Pb- and 208Pb(no Th)-corrected concordia diagrams and 204Pb-, 207Pb- and 208Pb(no Th)-corrected age channels can be calculated for user-specified initial Pb ratio(s). All other conventional common Pb correction methods (e.g. intercept or isochron methods on co-genetic analyses) can be performed offline. The approach was tested on apatite and titanite age standards (for which there are independent constraints on the U-Pb crystallization age) using a Thermo Scientific iCAP-Qc (Q-ICP-MS) coupled to a Photon Machines Analyte Excite 193 nm ArF Excimer laser. Madagascar apatite, OLT1 titanite and R10 rutile were used as primary standards and were corrected for variable common Pb using the new VizualAge_UcomPbine DRS. The secondary Durango (31.44 ? 0.18 Ma) apatite standard yielded a U-Pb TW concordia intercept age of 31.97 ? 0.59 Ma (MSWD = 1.09; primary standard corrected by the 207Pb-method) and a U-Pb concordia age of 31.82 ? 0.40 Ma (MSWD = 1.4; primary standard corrected by the 204Pb-method). McClure Mountain (523.51 ? 1.47 Ma) yielded a U-Pb TW concordia intercept age of 524.5 ? 3.7 Ma (MSWD = 0.72) while the Fish Canyon Tuff (28.201 ? 0.046 Ma) and Khan (522.2 ? 2.2 Ma) titanite standards yielded U-Pb TW concordia intercept ages of 28.78 ? 0.41 Ma (MSWD = 1.4) and 520.9 ? 3.9 Ma (MSWD = 4.2) respectively. The suitability of the 208Pb(no Th)-correction is demonstrated by the agreement between a U-Pb TW concordia intercept age of 452.6 ? 4.7 Ma (MSWD = 0.89) and a 208Pb(no Th)-corrected TW concordia age of 448.6 ? 4.5 Ma (MSWD = 1.4) on a c. 450 Ma rutile which exhibits variable incorporation of common Pb. A range of LA-ICPMS U-Pb dating applications are presented and include U-Pb dating of apatite from > 3.8 Ga gneisses from Akilia, SW Greenland. These apatites host 13C-depleted graphite inclusions that are interpreted as biogenic in origin and representing the oldest indications of life on Earth. The U-Pb age profiles on single apatite grains presented here are characteristic of Pb loss by volume diffusion with core-rim age differences of up to 300 Ma. These data explain the scatter and poor precision of earlier U-Pb apatite age determinations on Akilia apatite. Other LA-ICPMS dating applications include U-Pb apatite dating as a rapid method for determining the age of mafic intrusions, U-Pb titanite and apatite dating of ash fall tuffs, determining temperature-time histories using multiple U-Pb thermochronometers and improving concordance in LA-ICPMS primary zircon standard datasets by analysing young, common Pb-bearing primary zircon standards that have not accumulated significant radiation damage.
PUBLISHED
Keywords: U-Pb dating; common Pb; Smart & Sustainable Planet